2019
DOI: 10.1177/2156759x19882646
|View full text |Cite
|
Sign up to set email alerts
|

School Counselors’ Perceptions of Barriers to Implementing a RAMP-Designated School Counseling Program

Abstract: This study examined what school counselors perceive to be consistent barriers to implementing a program that adheres to the ASCA National Model. The Recognized ASCA Model Program (RAMP) designates such implementation. Principal component analysis revealed six common barriers: lack of confidence, lack of administrative support, time spent on clerical and office work, lack of teacher and parent support to implement aspects of the ASCA National Model, time spent on testing and monitoring, and time constraints. Lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(55 citation statements)
references
References 61 publications
(108 reference statements)
6
49
0
Order By: Relevance
“…Often, when someone needed to be assigned to testing, 504 coordination, scheduling, or other similar tasks, it frequently fell to the school counselor. Other researchers have had similar findings (Fye, Miller, & Rainey, 2018;Hilts, Kratsa, Joseph, Kolbert, Crothers, & Nice, 2019;Randick et al, 2019). Asking school counselors to do activities outside of the roles they were trained for has been shown to lead to stress, emotional exhaustion, burnout, role conflict, and career dissatisfaction (Holman, Nelson, & Watts, 2019;Kim & Lambie, 2018;McCarthy, Kerne, Calfa, Lambert, & Guzman, 2010;Semmer, Jacobshagen, Meier, Elfering, Beehr, Kälin, & Tschan, 2015).…”
Section: Discussionsupporting
confidence: 66%
“…Often, when someone needed to be assigned to testing, 504 coordination, scheduling, or other similar tasks, it frequently fell to the school counselor. Other researchers have had similar findings (Fye, Miller, & Rainey, 2018;Hilts, Kratsa, Joseph, Kolbert, Crothers, & Nice, 2019;Randick et al, 2019). Asking school counselors to do activities outside of the roles they were trained for has been shown to lead to stress, emotional exhaustion, burnout, role conflict, and career dissatisfaction (Holman, Nelson, & Watts, 2019;Kim & Lambie, 2018;McCarthy, Kerne, Calfa, Lambert, & Guzman, 2010;Semmer, Jacobshagen, Meier, Elfering, Beehr, Kälin, & Tschan, 2015).…”
Section: Discussionsupporting
confidence: 66%
“…The overemphasis on administrative duties is deleterious not only because it can contribute to occupational burnout and low job satisfaction (Holman et al, 2019), but also because it reduces time for implementing comprehensive school counseling programs (Fye et al, 2017;Hilts et al, 2019). These expectations to take on noncounseling work are especially prevalent in urban schools and those serving marginalized populations (Monteiro-Leitner et al, 2006), further perpetuating inequity by drawing counseling away from the most vulnerable students.…”
Section: Role Ambiguitymentioning
confidence: 99%
“…Practitioners are therefore unable to see themselves within RAMPspecific publications, causing the process to seem abstract and inaccessible. In line with the recommendations of previous literature (e.g., Hilts et al, 2019), this article serves to illuminate the RAMP process.…”
Section: Rationale For the Current Studymentioning
confidence: 53%
“…Actual ratios are often higher (ASCA, 2019b), which may affect quality of service delivery. In fact, Hilts and colleagues (2019) found that school counselors saw high ratios as a significant impediment to beginning the RAMP process. The findings of the current investigation, however, indicate that ratio alone should not be a hindrance to beginning or successfully completing the RAMP process.…”
Section: Discussion and Implications For Practicementioning
confidence: 99%